Effect of Tubewell and Sewage Water on Cadmium Adsorption Behaviour in Soils of Malwa Region of Madhya Pradesh - S.B. Aher and P.S. Rajput, D.S. Yashona, K.S. Bangar (Journal of the Indian Society of Soil Science, 2016)
A laboratory investigation was carried out to study the adsorption of cadmium (Cd) in surface and sub-surface samples of four different soils of district Indore, Madhya Pradesh. These samples were collected from 0-15 and 15-30 cm depths and representing Sarol series of Vertisol (Typic Haplusterts) and Malikheri series of Inceptisol (Fluventic Ustochrepts) irrigated with tubewell and sewage effluents. Soil samples with pH range of 7.3 to 8.0, were subjected to Cd treatment at various concentrations (0 to 90 mg L-1) and equilibrated at room temperature (25±1°C). Results indicated that the adsorption capacity of the soils for Cd was higher in Sarol, compared to Malikheri when irrigated with sewage effluents. All the 4 soils used in this study followed Langmuir adsorption isotherms. The adsorption maxima was higher in Sarol series irrigated with sewage effluents. The standard free energy (DG°) data showed the lowest values in Sarol series irrigated with sewage effluents (-15.5 and -13.8) for long run. It appears that Cd adsorption was more in soils having higher CEC values and organic matter content.